The effects of ACS (1-aminocyclopropane-l-carboxylate synthase) gene down regulation on ethylene production and fruit softening in transgenic apple - Galli, Zs.; Kiss, E.; Hrazdina, G.; Heszky, L. (International Journal of Horticultural Science, 2003)
A detailed examination of the production of ethylene and other ripening parameters during storage period has been undertaken in transgenic apple fruits, where the ethylene biosynthesis was inhibited by antisense ACS (l-aminocyclopropane-l-carboxylate synthase) gene. Data indicate down regulation of ethylene production, softening and spoilage in some transgenic lines. In some cases ethylene production was inhibited for over 90 percent, considerable reduction of softening and spoilage was observed probably due to the reduced activity of cell wall degradable enzymes. ACS activity was also monitored during ripening. The fruits of the best transgenic lines could be stored for minimum 4-5 months longer under 5 °C cold room storage conditions and one month longer at normal room temperature. This molecular approach can provide an alternative way to replace the commonly used and costly atmospheric storage of fruits.